Colocolic Hepatic Angle Intussusception due to Ascending Colon Giant Lipoma: A Case Report and a Review of Literature (International Journal of Clinical Research, 2022)
Background: Colon lipomas are rare benign lesions taking place mostly in the right colon with a female predomination. They are mainly submucosal and symptomatic when becoming more than 2 cm in size. Case Report: This is the case of a 43 years old female patient presenting with bowel obstruction associated with colocolic intussusception due to a giant colonic lipoma. A segmental partial colectomy has been performed followed by a favorable postoperative course. Conclusion: Giant colon lipomas presenting with intussusception is a rare finding. Surgery is the major treatment but, unfortunately, there is no clear consensus on the recommended procedure in the literature.